Spontaneous Malignant Transformation of a Pilocytic Astrocytoma of Cerebellum: Case Report. Issue 1 (5th March 2015) - Coelho, Joana; Nunes, Sofia; Salgado, Duarte
Pilocytic astrocytoma is a slowly growing neoplasia that represents the most frequent cerebral tumor in pediatric age. Malignant transformation is rare and it is usually related to previous radiotherapy. The authors describe a case of a spontaneous malignant transformation of a pilocytic astrocytoma. A 3-year-old boy was diagnosed with a cerebellar hemisphere tumor. He was submitted to a complete excision of the lesion, and histological findings were consistent with pilocytic astrocytoma. It was negative for p53. Twelve years later he presented with a local recurrence. Histopathological diagnosis was glioblastoma and it was positive for p53. Death from disease progression occurred 16 months after the diagnosis of glioblastoma. This case suggests that patients with pilocytic astrocytoma need closer follow-up and further genotypic studies in order to provide clues to clinical behavior. Such understanding can allow us to stratify treatment accordingly and to proceed to more aggressive treatment when necessary.